Analisis Kinerja Ditinjau Dari Kedisiplinan, Pengawasan Lingkungan Kerja - Yulianti, Prima; Masruri, Masruri (LPPM Universitas Dharma Andalas, 2024)
This study aims to analyze the influence of discipline, supervision and work environment on the performance of Pauh Padang sub-district employees. The population in this study was all employees of the Pauh Sub-district Sub-district of Padang City. Sampling was carried out by total sampling technique or saturated sample and distribution of questionnaires to 36 respondents. The data analysis technique uses multiple regression analysis. The results showed that (1) discipline has a positive and significant effect on performance, (2) supervision has a positive and significant effect on performance, (3) the work environment has a positive and significant effect on performance.